Smoking Behavioral Dependence during the COVID-19 Pandemic Among University Student - Vania Dwi Ramadhani; Laili Rahayuwati; Mamat Lukman (Jurnal Berita Ilmu Keperawatan, 2023)
Smoking, an addictive behaviour, is a health problem that is still found during the COVID-19 pandemic. There are several possibilities that have impacts on smoking behaviour during the COVID-19 pandemic. The aim of this study is to understand the description of smoking addiction during the COVID-19 pandemic towards students at the University. A descriptive quantitative research design was used. This study involved one variable which is smoking behavioral dependence during the COVID-19 pandemic in students at the University. The populations in this study are students who are active smokers (conventional, electric, or shisha) at one of the universities in Indonesia. The sampling technique uses accidental sampling, and it is obtained a sample of 378 students. The instrument in this study uses the GN-SBQ (Glover Nilsson-Smoking Behavioural Questionnaire). The results of the research data are analyzed using descriptive analysis in the percentage frequency distribution. Based on the results of the study, it is found that during the COVID-19 pandemic, most of the respondents experienced smoking dependency behavioral moderate (66.4%), strong (20.9%), and mild (12.7%). The use of cigarettes during the COVID-19 pandemic mostly uses conventional rather than electric and shisha. Based on the characteristics of the respondents, smoking behavioral dependency is dominated by male students, aged 21 years, grade 2017, and had pocket money in the middle economic category. Therefore, this study recommends health services to provide counselling and mentoring services for students, which one of them is the Cognitive Behavioral Therapy (CBT) approach to reduce the level of smoking behavior.